Ritual Wong-wongan Sebagai Upaya Masyarakat Bali dalam menghadapi Pandemi Covid-19 (Analisis Teori Simbol dalam Pendekatan Antropologi) - Datin Rafiliah (An-Nas, 2021)
Amidst the pandemic, the Indonesian government has issued some regulations to reduce the transmission of Covid-19. At the same time, there are rituals from various regions that are believed to be a method to ward off threats, calamities, or diseases. In this study, the author examines a ritual known as Wong-wongan, which is performed by the Balinese to deal with the pandemic. The researcher conducted a qualitative study, which is library research with books and other literature as the primary object. The result of this discussion is that it is called wong-wongan rice because this ritual provides offerings that are placed in the yard of the house's entry in a cooked form, specifically rice in the shape of wong-wongan (people). This offering also includes a variety of additional ingredients, including onions, ginger, salt, and prickly pandan leaves, which are some of the symbols of weapons used to ward off evil. Everything is arranged on the tip of a banana leaf sheet. With tools or materials, as well as other symbols that reflect certain characteristics in this ceremony, it provides an understanding in the Anthropological approach, specifically on the symbol theory provided by various anthropologists such as Raymond Firth, Geertz, and others. According to Geertz, the analysis of rituals, traditions, and ceremonies in any form carried out by the Balinese people, or those outsides of them, is not just a set of values whose place is outside of humans, but also a system of knowledge and a system of symbols that permits meaning to exist. A symbol can transform knowledge into value and value into knowledge.